2013
DOI: 10.7567/jjap.52.04cp04
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Al Memory-Effect on Growing 4H-SiC Epilayers by Hot-Wall Chemical Vapor Deposition

Abstract: The study of the parameters' distribution along the channel axis in a stationary plasma thruster(SPT) helps one to understand the physical characteristics of the SPT's operation. In this paper, the axial distribution of the desired SPT parameters are predicted by combining the improved scaling theory and a one-dimensional hybrid model. The simulation indicates that the SPT parameters' distribution along the channel axis changes with scaling index variable C. If C is set properly, the similarity of the paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Therefore, we performed site-competition growth (Si-rich) to further reduce Al impurity level by hindering Al atom incorporation during the undoped epilayer growth. 7,[12][13][14][15] Undoped epilayers were grown at C/Si = 0.2-0.8, with a 5 min HCl flushing inserted between the epilayers growth at the HCl flow rates of 20, 200, and 400 sccm. To minimize the effect of residual HCl gas on the following undoped epilayer growth, there was an additional waiting period (only H 2 in) of 3-5 min to purge the remaining HCl gas in the reactor.…”
Section: Hcl Flushing Followed By Site-competition Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we performed site-competition growth (Si-rich) to further reduce Al impurity level by hindering Al atom incorporation during the undoped epilayer growth. 7,[12][13][14][15] Undoped epilayers were grown at C/Si = 0.2-0.8, with a 5 min HCl flushing inserted between the epilayers growth at the HCl flow rates of 20, 200, and 400 sccm. To minimize the effect of residual HCl gas on the following undoped epilayer growth, there was an additional waiting period (only H 2 in) of 3-5 min to purge the remaining HCl gas in the reactor.…”
Section: Hcl Flushing Followed By Site-competition Growthmentioning
confidence: 99%
“…Much research effort has been made to suppress the Al memory effect. [7][8][9][10][11] We have studied the suppression methods using site-competition growth and achieved a reduction factor (the ratio of Al concentration N Al in the undoped epilayer to that in the p + layer) of about 1/17,000, e.g., N Al from 9 © 10 19 to 6 © 10 15 cm ¹3 or from 1.7 © 10 20 to 1.0 © 10 16 cm ¹3 . 7) On the other hand, La Via et al reported that the growth using trichlorosilane can decrease the Al impurity level to 10 14 cm ¹3 after a p + epilayer growth with N Al ³ 1 © 10 18 cm ¹3 , but it is a concern that there may be an upper limit of Al doping level of approximately 10 18 cm ¹3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the as called "memory effect" in MOCVD, described in literature [142], [143], it is very much different from this case. Memory effect refers to abrupt change in gas-phase composition during growth, i.e when growing GaN:Mg (Mg-doped, with Ga/Mg ratio usually <1000) followed by undoped GaN (without intentional doping, Mg-is off).…”
Section: D-gan Formation-interpretation-propertiesmentioning
confidence: 86%